2022
DOI: 10.1039/d2nr02711a
|View full text |Cite
|
Sign up to set email alerts
|

Hansen parameter evaluation for the characterization of titania photocatalysts using particle size distributions and combinatorics

Abstract: Titania photocatalysts have great potential as remidiators of air pollution. While various aspects of photocatalyst synthesis, adsorption and photoactivity have been investigated, thorough understanding of the particle surface behavior has...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(18 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…For accurate analysis, it is important to be able to determine HSPs properly. In this work, the HSPs of P25, CB, and Si/C were derived via two different methods-IEA and PSDC-based on the works of Süß et al and Anwar et al [18,21] The results show that the methods chosen lead to similar HSPs. It has been further shown that the steps to end up in a consistent PL categorization, and thus the resulting PL list has a major effect on the observed and remaining differences in the finally derived HSPs.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…For accurate analysis, it is important to be able to determine HSPs properly. In this work, the HSPs of P25, CB, and Si/C were derived via two different methods-IEA and PSDC-based on the works of Süß et al and Anwar et al [18,21] The results show that the methods chosen lead to similar HSPs. It has been further shown that the steps to end up in a consistent PL categorization, and thus the resulting PL list has a major effect on the observed and remaining differences in the finally derived HSPs.…”
Section: Discussionmentioning
confidence: 95%
“…In contrast, the PSDC method uses combinatorics which calculates all possible combinations with a good fit, and any bad fit is neglected. [20,21] In addition, the resulting HSP reporting summary, here provided as a best-practice-example, includes all the data needed to form an informed opinion about the data of the material analyzed. A general trend observed was that the PSDC method results in smaller HSP spheres and therefore enables to better differentiate between variations of the same material.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations